Operative debitomanometry and common bile duct stones - Delgado, Bolivar; Perrier, José P. (Cirugía del Uruguay, 1979)
Based on 50 cases of common bile duct lithiasis the authors evaluate intraoperatory debitomanometry in diagnosis of this condition. In this series; there is considerable variation in debitomanometric figures with predominance of normal values. Hypertonic curves in cases of associated pathology ( stenosing papillitis and chronic pancreatítis) are frequent and the "bl"ockade syndrome" is valuable in diagnosis of papillary Jithiasis.